Dispersion characteristics of nanometer-scaled silicon nitride suspended membrane waveguides*Project supported by the National Natural Science Foundation of China (Nos. 61435002, 61527823 61321063). (November 2016) - Bian 边, Dandan 丹丹; Lei 雷, Xun 勋; Chen 陈, Shaowu 少武
Abstract: We investigate the dispersion properties of nanometer-scaled silicon nitride suspended membrane waveguides around the communication wavelength and systematically study their relationship with the key structural parameters of the waveguide. The simulation results show that a suspended membrane waveguide can realize anomalous dispersion with a relatively thinner silicon nitride thickness in the range of 400 to 600 nm, whereas, for the same membrane thickness, a conventional rib or strip silicon nitride waveguide cannot support anomalous dispersion. In particular, a waveguide with 400 nm silicon nitride thickness and deep etch depth ( r = 0.05) exhibits anomalous dispersion around the communication wavelength when the waveguide width ranges from 990 to 1255 nm, and the maximum dispersion is 22.56 ps/(nm·km). This specially designed anomalous dispersion silicon nitride waveguide is highly desirable for micro-resonator based optical frequency combs due to its potential to meet the phase-matching condition required for cascaded four-wave-mixing.